NC machining verification algorithm based on the STL model - Miao, Ying; Song, Xiaowen; Wang, Jun; Lu, Zhonghua (International journal of advanced manufacturing technology, 2020)
An algorithm to assess the deviation of a machined workpiece model for a nominal part of the stereolithography (STL) model-based numerically controlled (NC) machining verification is presented, which is inspired by several algorithms used for evaluating the difference between two triangular meshes of similar shape, and some improvements are made. First, each triangle of the machined workpiece model is sampled under a user-defined sampling step δ . Then, the signed distance between each sample and the nominal part is computed to obtain the maximal error, minimal error, and mean error between the two STL models. Finally, a background grid is constructed to quickly search for the triangle closest to the sampling point. The experimental results demonstrate that the accuracy can be improved by sampling all the triangles, including those too small to be sampled under the current sampling step δ . The efficiency can be increased by applying a background grid, and the undercut and overcut areas can be easily detected by coloring the machined workpiece model according to the signed distance associated with each sample.